Identification of Outer Membrane Proteins Altered in Response to UVC-Radiation in Vibrio parahaemolyticus and Vibrio alginolyticus - Abdallah, Fethi Ben (Springer-Verlag, 2012)
Vibrio parahaemolyticus and V. alginolyticus, marine foodborne pathogens, were treated with UVC-radiation (240 J/m(2)) to evaluate alterations in their outer membrane protein profiles. Outer membrane protein patterns of UVC-irradiated bacteria were found altered when analyzed by sodium dodecyl sulphate polyacrylamide gel electrophoresis. Altered proteins were identified by mass spectrometry (MS and MS/MS) and analysis revealed that OmpW, OmpA, Long-chain fatty acid transport protein, Outer membrane receptor protein, Putative uncharacterized protein VP0167, Maltoporin (lamB), Polar flagellin B/D, Agglutination protein Peptidoglycan-associated lipoprotein and MltA-interacting protein MipA were appeared, thereby they can be considered as UVC-stress proteins in some vibrios. In addition, expression of OmpK decreased to non-detectable level. Furthermore, we observed a decrease or an increase in the expression level of other outer membrane proteins.